'Undecidability' or 'anticipatory resoluteness' Caputo in conversation with Heidegger - Avakian, Sylvie 1969- (2015)
In this article I will consider John D. Caputo's 'radical hermeneutics', with 'undecidability' as its major theme, in conversation with Martin Heidegger's notion of 'anticipatory resoluteness'. Through an examination of the positions of Caputo and Heidegger I argue that Heidegger's notion of 'anticipatory resoluteness' reaches far beyond the claims of 'radical hermeneutics', and that it assumes a reconstructive process which carries within its scope the overtones of deconstruction, the experience of repetition and authenticity and also the implications of Gelassenheit. Further, I am arguing that Caputo's 'radical hermeneutics' is problematic and even erroneous when it comes to criticize Heidegger's thought portraying it as being founded on 'the myth of the early Greeks'.
Keywords: Anticipatory resoluteness; CAPUTO, John D; Christian Theology; DETERMINATION (Personality trait); Heidegger, Martin, 1889-1976; Hermeneutics; John D. Caputo; Martin Heidegger; Radical hermeneutics; Religion -- Philosophy; Undecidability